(untitled) (Research, Society and Development, 2022)
Short implants are an excellent alternative for the treatment of atrophic alveolar ridges. The advantages, compared to other techniques proposed for rehabilitation through posterior mandible implants, include the reduction of morbidity, treatment time and costs. Therefore, the aim of this study is to evaluate the importance of using short implants for the rehabilitation of atrophic mandibles, in order to provide support for the current literature. It is a Literature Literature Review, narrative type, developed through bibliographic analysis in the databases: PubMed/Medline, Scielo, Academic Google, VHL (Virtual Health Library). After applying the search strategy in the databases and the eligibility criteria, 24 articles were included in this study. Based on the consulted literature, it was observed that short implants have similar success rates to long implants. In addition, the use of short implants favors benefits, eliminating bone graft surgeries in atrophic areas. However, the use of reduced size implants may be contraindicated in patients with local or systemic diseases. In this sense, when the use of short implants is recommended, a correct surgical protocol must be carried out to ensure a better longevity to the proposed treatment.